Defect‐Driven Magnetization Configuration of Isolated Linear Assemblies of Iron Oxide Nanoparticles. (9th September 2019) - Rastei, Mircea V.; Pierron‐Bohnes, Véronique; Toulemon, Delphine; Bouillet, Corinne; Kákay, Attila; Hertel, Riccardo; Tetsi, Ebenezer; Begin‐Colin, Sylvie; Pichon, Benoit P.
Abstract: The magnetization state of 1D magnetic nanoparticle (NP) chains plays a key role in a wide range of applications ranging from diagnosis and therapy in medicine to actuators, sensors, and quantum recording media. The interplay between the exact particle orientation and the magnetic anisotropy is in turn crucial for controlling the overall magnetization state with high precision. Here, a 3D description of the magnetic structure of one‐NP‐wide chains is reported. Here, two complementary experimental techniques are combined, magnetic force microscopy (MFM) and electronic holography (EH) which are sensitive to out‐of‐plane and in‐plane magnetization components, respectively. The approach to micromagnetic simulations is extended, which provides results in good agreement with MFM and EH. The findings are at variance with the known results on unidirectional NP assemblies, and show that magnetization is rarely strictly collinear to the chain axis. The magnetic structure of one‐NP‐wide chains can be interpreted as head‐to‐head magnetic domain structures with off‐axis magnetization components, which is very sensitive to morphological defects in the chain structure such as minute size variation of NPs, tiny misalignment of NPs, and/or crystal orientation with respect to easy magnetization axis. Abstract : A 3D description of the magnetic structure of one‐nanoparticle‐wide chains is provided by combining magnetic force microscopy, electronic holography, high‐resolution transmission electron microscopy, and micromagnetic simulations. The magnetic structure is interpreted as head‐to‐head magnetic domain structures with off‐axis magnetization components, which is very sensitive to morphological defects in the chain structure.